Minimally-invasive neck dissection and free flap reconstruction in patients with cancer of the head and neck. Issue 1 (January 2017) - Hsu, D.W.K.; Sayan, A.; Ramchandani, P.; Ilankovan, V.
Abstract: We describe our experience of cervical lymphadenectomy with microvascular anastomoses involving levels I to V through a minimally-invasive neck dissection. We retrospectively studied 12 patients who had levels I to IV neck dissection with free flap reconstruction between July 2013 and April 2015 at Poole Hospital (male:female ratio 8:4, mean (range) age 66 (49 – 83) years). The mean (range) operating time was 7 (5 – 8) hours, and the total volume drained from the neck was 105 (60-300) ml. The mean (range) number of harvested lymph nodes was 26 (13-39) from levels I to III, and 33 (20-42) from levels I to IV. Four patients developed weakness of the marginal mandibular nerve, but there were no serious complications. All flaps were successful, there was no regional recurrence, and most patients were discharged on postoperative day 15. This technique provides adequate exposure for lymphadenectomy and anastomosis, and we think that head and neck surgeons should include it in the armamentarium of reconstruction.